2020
DOI: 10.1200/jco.19.00126
|View full text |Cite
|
Sign up to set email alerts
|

Adding Ovarian Suppression to Tamoxifen for Premenopausal Breast Cancer: A Randomized Phase III Trial

Abstract: PURPOSE The addition of ovarian function suppression (OFS) for 5 years to tamoxifen (TAM) for treatment of premenopausal patients with breast cancer after completion of chemotherapy has beneficial effects on disease-free survival (DFS). This study evaluated the efficacy of adding 2 years of OFS to TAM in patients with hormone receptor–positive breast cancer who remain in a premenopausal state or resume ovarian function after chemotherapy. PATIENTS AND METHODS We enrolled 1,483 premenopausal women (age ≤ 45 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 21 publications
1
61
0
2
Order By: Relevance
“…The significantly higher RFS event rates associated with high intratumoral CYP27A1 expression in patients < 55 years (pre-and perimenopausal) presenting with ER+ tumors during the first 5 years after BC diagnosis in BC-blood is intriguing since the logical expectation is that high 27HC should display antagonistic properties under estrogenic conditions and therefore be protective in premenopausal patients, a premise which was verified in our previous study [39] reporting a significant improved RFS and OS for younger patients (< 50 years old) presenting with high compared with low CYP27A1 mRNA in their tumors. Several studies have reported the benefit of suppressing ovarian function in premenopausal patients receiving endocrine therapies [48][49][50], and it is also well established that chemotherapy treatment can induce a postmenopausal physiological state in some premenopausal patients [51,52]. The more generous prescription of chemotherapy in BC-blood and the higher likelihood that ovarian function suppressants may have been prescribed for patients in BC-blood given the more recent recruitment of patients into this cohort may to some extent explain the observed inverse association between high CYP27A1 and survival among the younger patients in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The significantly higher RFS event rates associated with high intratumoral CYP27A1 expression in patients < 55 years (pre-and perimenopausal) presenting with ER+ tumors during the first 5 years after BC diagnosis in BC-blood is intriguing since the logical expectation is that high 27HC should display antagonistic properties under estrogenic conditions and therefore be protective in premenopausal patients, a premise which was verified in our previous study [39] reporting a significant improved RFS and OS for younger patients (< 50 years old) presenting with high compared with low CYP27A1 mRNA in their tumors. Several studies have reported the benefit of suppressing ovarian function in premenopausal patients receiving endocrine therapies [48][49][50], and it is also well established that chemotherapy treatment can induce a postmenopausal physiological state in some premenopausal patients [51,52]. The more generous prescription of chemotherapy in BC-blood and the higher likelihood that ovarian function suppressants may have been prescribed for patients in BC-blood given the more recent recruitment of patients into this cohort may to some extent explain the observed inverse association between high CYP27A1 and survival among the younger patients in this cohort.…”
Section: Discussionmentioning
confidence: 99%
“…57,59,60 While negative results emerged from the E-3193 INT-0142 study, probably due to the small sample size and the low-risk population included, 59 an improvement in terms of DFS and OS by adding OFS to tamoxifen was observed in both the ASTRRA and SOFT studies. 58,61 In the ASTRRA trial, a total of 1289 premenopausal patients with hormone receptor-positive breast cancer were randomly allocated to receive tamoxifen alone for 5 years or tamoxifen for 5 years plus OFS for 2 years. 58 Median age was 39 years and 53% of the patients had nodal involvement.…”
Section: Ofs Plus Tamoxifenmentioning
confidence: 99%
“…58,61 In the ASTRRA trial, a total of 1289 premenopausal patients with hormone receptor-positive breast cancer were randomly allocated to receive tamoxifen alone for 5 years or tamoxifen for 5 years plus OFS for 2 years. 58 Median age was 39 years and 53% of the patients had nodal involvement. All patients in this study were previously exposed to adjuvant or neoadjuvant chemotherapy and had to have a recovery of ovarian function within 2 years after the end of cytotoxic treatment for being eligible to the trial.…”
Section: Ofs Plus Tamoxifenmentioning
confidence: 99%
See 1 more Smart Citation
“…Таким образом, пременопаузальные женщины с HR-позитивным/HER2-негативным РМЖ высокого риска по клинико-патомофрологическим характеристикам могут достичь от 10 до 15% абсолютного улучшения 8-летней безметастатической выживаемости благодаря адъювантной гормонотерапии эксеместаном + OFS в сравнении с терапией тамоксифеном + OFS или одним тамоксифеном [1,2,12].…”
Section: Introductionunclassified